O impacto da confiança na marca e do Technology Readiness Index (Tri 2.0) na disposição de uso de carros autônomos - Pinto Filho, José Carlos Rodrigues (2018)
The arrival of autonomous vehicles (AVs) at the world automotive market will result in considerable changes in a century-old industry. The transfer of tasks and responsibilities to the machine, however, brings a number of open questions, ranging from the impact on the labor market to the quest for lesser evil in unavoidable accidents; this set of factors could be decisive in the acceptance and adoption of such technology that places traditional automakers - such as Ford, GM and Volvo, among others - in competition with Information Technology companies such as Google, Apple and Uber. Reviewing the main models of innovation adoption and diffusion, none of them considers brand trust as a potential influencer of positive or negative attitudes in adopting new technologies. Thus, through a quantitative approach and research survey method with potential consumers, this project sought to analyze whether brand trust (using Gurviez and Korchia's multidimensional confidence model, 2003) influences the Technology Readiness Index (TRI) (Parasuraman Colby, 2001), in its updated version (TRI 2.0, by Parasuraman and Colby, 2015), in the provision of use of AVs in a generic approach and applied to 11 selected brands. After validating the scales for internal consistency, the results, based on 213 respondents (n=213), indicated that there is a strong correlation between the TRI and the overall AV willingness to use (p=0,000), as well as between brand confidence and willingness to use AVs of this same brand. When confronted through multiple linear regression, brand trust plays a more relevant role than TRI in AV’s willingness-to-use for the 11 brands tested (while TRI was significant only for the brand Tesla). Comparing information technology companies (ITCs) and automobile manufacturers, while the first presents a higher level of average confidence (Apple having the highest index, followed by Google and Toyota), the predilection in AV’s willingness-to-use falls on traditional automakers (with Tesla having the best index, followed by Toyota and, then, Apple).